A high‐impact meso‐beta vortex in the Adriatic Sea. (7th February 2023) - Miglietta, Mario Marcello; Buscemi, Federico; Dafis, Stavros; Papa, Alvise; Tiesi, Alessandro; Conte, Dario; Davolio, Silvio; Flaounas, Emmanouil; Levizzani, Vincenzo; Rotunno, Richard
Abstract: On the evening of November 12, 2019, an exceptional high tide – the second‐highest in the ranking since sea‐level data have been recorded – hit the city of Venice in northern Italy and its entire lagoon, damaging a large part of its historical center. A small warm‐core mesoscale cyclone, which formed in the central Adriatic Sea and intensified during its northwestward movement toward the Venice lagoon, was responsible for the event. The cyclone was preceded by intense northeasterlies (Bora) in the northern Adriatic, which turned to southeasterlies (Sirocco) and then southwesterlies after its passage. Simulations with different initialization times were carried out with the Weather Research and Forecasting (WRF) model. Simulation results show a strong sensitivity to the initial conditions, since the track (and strength) of the cyclone was determined by the exact position of an upper‐level potential vorticity (PV) streamer. The factors responsible for the cyclone development and its characteristics are also investigated. The pre‐existence of positive low‐level cyclonic vorticity, associated with the convergence of the Sirocco and Bora winds in the central Adriatic, made the environment favorable for cyclone development. Also, the interaction between the upper‐level PV anomaly and the low‐level baroclinicity, created by the advection of warm, humid air associated with the Sirocco, was responsible for the cyclone's intensification, in a manner similar to a transitory (stable) baroclinic interaction at small horizontal scales. Sensitivity experiments reveal that convection, latent heat release and sea‐surface fluxes did not play a significant role, indicating that this cyclone did not show tropical‐like characteristics, notwithstanding its low‐level warm core. Thus, the warm‐core feature appears mainly as a characteristic of the environment in which the cyclone developed rather than a consequence of diabatic processes. Lastly, the cyclone does not fall into any of the existing categories for Adriatic cyclones. Abstract : At about 2100 UTC, November 12, 2019, a small warm‐core cyclone, formed in the central Adriatic Sea, made landfall near Venice and was responsible for an exceptional high tide. Convection and sea‐surface fluxes did not play a significant role in the cyclone development, notwithstanding its low‐level warm core. Conversely, the interaction between the upper‐level PV anomaly and the low‐level baroclinicity was responsible for its intensification, in a manner similar to a transitory (stable) baroclinic interaction at small horizontal scales.